2019
DOI: 10.1103/physrevb.100.075424
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of the charge-driven phase transition in group-VI transition metal dichalcogenides

Abstract: Materials exhibiting multiple stable phases can be used as functional components in electronic and optical applications if the phase transition is controllable. Group-VI transition metal dichalcogenides (TMDs, MX2, where M=Mo, W and X = S, Se) are known to undergo charge induced transitions from semi-conducting H phases to metallic T phases. This occurs, for example, when bulk TMDs are exfoliated with the aid of alkali ion intercalants. However, it is difficult to experimentally decouple the effect of composit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 74 publications
(67 reference statements)
5
19
0
Order By: Relevance
“…Note that besides our own report 17 on the consequences of these unphysical approaches to electrostatics for chemisorption in the literature, similar observations were recently made in the context of electrochemical barriers 32 and chargedriven phase transitions. 33…”
Section: General Methodologymentioning
confidence: 99%
“…Note that besides our own report 17 on the consequences of these unphysical approaches to electrostatics for chemisorption in the literature, similar observations were recently made in the context of electrochemical barriers 32 and chargedriven phase transitions. 33…”
Section: General Methodologymentioning
confidence: 99%
“…Note that this process is reversible, those intercalated metallic TMDs tend to back to 2H phase as the intercalants are removed through annealing or aging. Previous work has calculated the transition barriers of MoS 2 , MoSe 2 , WS 2 , and WSe 2 with different lithium ions intercalation concentration, [ 37 ] and it indicates that there is a distinct decrease of transition barriers for all the four materials after lithium‐ion intercalation, which may be the reason why lithium ions intercalation could trigger the phase transition. However, lithium ions intercalation cannot eliminate transition barrier completely but to decrease it and there is still a barrier of 0.24 eV for the smallest distance from H‐phase to T′‐phase (Li 1 WSe 2 ).…”
Section: Preparationmentioning
confidence: 99%
“…[ 4,16,17 ] For most group VI TMDCs, with the exception of WTe 2 , the trigonal prismatic 2H phase is thermodynamically more stable than the octahedral 1T or distorted 1T′ phase with the energy difference (Δ E ) ranging from 0.84 eV in monolayer MoS 2 to 0.04 eV in monolayer MoTe 2 per unit formula. [ 4,16,17 ] While the exact values of the energy difference vary among different DFT calculations, all of the calculations show the same trend: the energy difference between the two phases is the largest for the sulfides and smallest for the tellurides. Thus, it might be expected that the 2H → 1T′ phase transition is most difficult for the sulfides and easiest for the tellurides.…”
Section: Knowledge Gap In Current Understanding Of Phase Transition and Intercalationmentioning
confidence: 99%
“…They found that Li adsorption leads to a decreased energy barrier for the 2H → 1T′ phase transition, and the energy difference, E 2H − E 1T′ , becomes positive above the threshold Li loading. [ 17 ] Another theoretical work showed that the undistorted 1T phase is an intermediate phase on the pathway from 2H to 1T′ in monolayer MoS 2 , and the transition from 1T to 1T′ occurs spontaneously with an almost zero activation energy, as shown in Figure 2B. [ 14 ]…”
Section: Knowledge Gap In Current Understanding Of Phase Transition and Intercalationmentioning
confidence: 99%
See 1 more Smart Citation